Two Randomized, Double-masked, Placebo-controlled Studies of the Local Anesthetic Effect of Articaine Ophthalmic Solution - Gonzalez VH; Wirta DL; Uram M; Schupp A; Widmann M; Novack GD (Clinical Ophthalmology, 2023)
Victor H Gonzalez,1 David L Wirta,2 Martin Uram,3 Audrey Schupp,4 Michelle Widmann,5 Gary D Novack6,7 1Valley Research Institute, McAllen, TX, USA; 2Eye Research Foundation, Newport Beach, CA, USA; 3American Genomics, LLC, Hobe Sound, FL, USA; 4CMC Turnkey Solutions, Bailey, CO, USA; 5Cal Clinical Solutions, Apex, NC, USA; 6PharmaLogic Development, Inc., San Rafael, CA, USA; 7Department of Ophthalmology & Vision Science, University of California, Davis, School of Medicine, Sacramento, CA, USACorrespondence: Gary D Novack, PharmaLogic Development, Inc., 17 Bridgegate Drive, San Rafael, CA, 94903, USA, Tel +1 415 472-2181, Email gary_novack@pharmalogic.comBackground: We wanted to develop a new topical ocular anesthetic with good bioavailability in anterior segment tissues. Given concerns about contamination and sterility in multi-dose products, we selected a unit-dose, nonpreserved presentation of AG-920 (articaine ophthalmic solution) in blow-fill-seal containers (similar to currently marketed pharmacological therapies for dry eye disease).Methods: Consistent with US Food and Drug Administration guidance, two pivotal, Phase 3, randomized, placebo-controlled, double-masked, parallel design studies conducted at two US private practices in 240 healthy subjects. A single dose of AG-920 or identical looking placebo into one (study) eye (2 drops 30 s apart). Subjects underwent a conjunctival pinch procedure and assessment of the pain associated with the pinch. The main outcome measure was the proportion of subjects with rating of “No pain at 5 minutes”.Results: AG-920 provided a rapid onset of local anesthesia (less than one minute) with clinically and statistically significantly greater effect in AG-920 (68% and 83%) than placebo (3% and 18% for Study 1 and Study 2, respectively, P< 0.0001). The most frequent adverse event was instillation site pain (27% vs 3%) followed by conjunctival hyperemia (probably related to the pinch, 9% vs 10%) in the AG-920 and placebo groups, respectively.Conclusion: AG-920 was found to be have a rapid onset and useful duration of local anesthesia with no major safety issues, and may be useful for the eye-care professional. Registered with clinicaltrials.gov as NCT04513652 and NCT04829344.Keywords: local anesthesia, articaine, controlled trial